Coal-based hollow carbon fiber membrane as well as preparation method and application thereof
By adjusting the bolus injection speed of the core layer spinning solution, the coal-based hollow carbon fiber membrane was prepared, which solved the problems of low desalination capacity and side reactions of existing carbon materials in capacitance deionization technology, and achieved higher desalination performance and structural stability.
Patent Information
- Application Number
- CN202411811223.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing carbon materials have low desalination capacity and side reaction problems in capacitance deionization technology, which affects their application effect.
By adjusting the bolus injection speed of the core layer spinning solution, coal-based hollow carbon fiber membranes with different inner diameters were prepared, and the ions migration ability was improved by using their large pore structure and high specific surface area, and mechanical properties and electrical conductivity were improved through coal oxidation modification.
The desalination capacity and desalination rate of carbon-based electrode materials are significantly improved, the negative impact of the binder on electrochemical properties is avoided, and the service life and structural stability of the electrode are improved.
Smart Images

Figure CN119615421A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment, and in particular relates to a coal-based hollow carbon fiber membrane and a preparation method and application thereof. Background Art
[0002] Fresh water accounts for only 2.53% of the world's water reserves, and only 13% of these fresh water resources can be directly used by humans. At the same time, climate change and population growth have also had a negative impact on drinking water from natural water resources such as rivers. In this case, brackish water is considered an ideal source of water for conversion into fresh water as an alternative water resource. In order to desalinate brackish water, people have explored various desalination processes, such as reverse osmosis, nanofiltration, and electrodialysis. These processes face difficulties such as high energy consumption and membrane degradation caused by scaling in practical applications. Capacitive deionization has become one of the ideal technologies for seawater desalination because of its advantages such as no secondary pollution, easy regeneration, long cycle life, and low energy consumption. Capacitive deionization technology is an electrochemical ion separation technology that uses porous carbon electrodes and is achieved through repeated adsorption and desorption processes, namely desalination and concentration.
[0003] As the core component of capacitive deionization technology, electrode materials have a direct impact on the development of capacitive deionization technology. The traditional method of preparing electrode materials is cumbersome and requires the addition of conductive agents and binders. The active material is mixed and ground with a certain proportion of conductive agent and polymer binder, and then attached to the collector. If the active material is unevenly distributed, the inevitable agglomeration may block some pores, affect electron transfer and ion transport, and further seriously affect the electrochemical reaction of the electrode material, ultimately leading to insufficient utilization of the electrode material and adversely affecting the cycle performance.
[0004] In addition, many traditional carbon materials generally have low desalination capacity and side reactions (common ion rejection and oxidative corrosion), which limit their practical application in capacitive deionization. Therefore, it is urgent to develop new materials or improve existing materials to improve their electrochemical performance; further, electrode materials, as the core part of capacitive deionization, can also effectively improve the CDI performance of carbon materials by regulating pore structure and building self-supporting structures. Summary of the invention
[0005] In view of the above technical problems, the present invention proposes a coal-based hollow carbon fiber membrane and its preparation method and application. The present invention adjusts the injection speed of the core layer spinning solution to prepare coal-based hollow carbon fiber membranes with different inner diameters, which exhibit good conductivity and capacitance properties and show many advantages in the field of capacitive deionization. The specific surface area of the coal-based hollow carbon fiber membrane prepared by the present invention can reach 378.30cm 2 g -1The macroporous structure of the coal-based hollow carbon fiber membrane can provide more space for ions to enter the electrode, which is beneficial to the migration of ions; the desalination capacity is 37.22 mg g -1 , is a solid coal-based carbon fiber (23.12 mg g -1 ) and the desalination rate reached 3.02 mg g -1 min -1 ). It can be seen from this that the coal-based hollow carbon fibers prepared by the present invention significantly improve the desalination capacity and desalination rate of the carbon-based electrode materials.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for preparing a coal-based hollow carbon fiber membrane comprises the following steps:
[0009] According to the injection speed ratio of the shell layer spinning solution and the core layer spinning solution being 18:(1-6), a hollow fiber precursor is collected on an aluminum foil by a coaxial electrospinning method, and then pre-oxidized and carbonized in sequence to obtain the coal-based hollow carbon fiber membrane;
[0010] The shell spinning solution contains oxidized coal and polyacrylonitrile;
[0011] The core spinning solution contains polystyrene.
[0012] Beneficial effects: The present invention adopts coaxial electrospinning to prepare coal-based hollow carbon fiber precursors. By fixing the injection speed of the shell layer spinning solution and adjusting the injection speed of the core layer spinning solution, coal-based hollow carbon fiber membranes with different inner diameters can be prepared. Among them, the hollow structure has a larger specific surface area and rich pore structure, which can provide more active sites.
[0013] Preferably, the injection speed ratio is 18:1, 9:1, 6:1, 9:2, 18:5, or 3:1.
[0014] Preferably, the total concentration of oxidized coal and polyacrylonitrile in the shell spinning solution is 10 to 20 wt %;
[0015] The polystyrene concentration in the core layer spinning solution is 20-30wt%.
[0016] Furthermore, the mass ratio of the oxidized coal to polyacrylonitrile is 1:1.
[0017] Further, the shell spinning solution is obtained by adding oxidized coal and polyacrylonitrile to N,N-dimethylformamide and magnetically stirring at 50-70° C. for 12-24 hours until completely dissolved;
[0018] The core layer spinning solution is obtained by adding polystyrene into N,N-dimethylformamide and magnetically stirring at 50-70° C. for 12-24 hours until the polystyrene is completely dissolved.
[0019] Preferably, the condition parameters during the coaxial electrospinning process are:
[0020] The injection speed of the shell spinning solution is 0.1-1.0 mm min -1 The core layer spinning solution injection speed is 0.005~0.34mm min -1 ; The positive and negative voltages are set to 10-22 kV and -3.0-0 kV respectively; the aluminum foil is placed on a roller, and the roller speed is 50-150 r min -1 , the receiving distance is 10~25cm.
[0021] Preferably, the conditions in the pre-oxidation process are:
[0022] In air atmosphere, at 2℃min -1 The temperature was raised from room temperature to 280°C and the pre-oxidation treatment was performed at this temperature for 1 hour.
[0023] Beneficial effects: During the pre-oxidation stage, the oxygen-containing functional groups on the surface of the oxidized coal promote the cyclization and cross-linking of polyacrylonitrile molecules, further stabilize the fiber structure, reduce the breakage and shrinkage of the molecular chains, and thus improve the thermal stability of the fiber.
[0024] Preferably, the conditions during the carbonization process are:
[0025] In an inert atmosphere, at 5 °C min -1 The temperature was raised from room temperature to 800°C and carbonized at this temperature for 2 h.
[0026] Beneficial effects: During the carbonization stage, the cross-linked network structure of the shell layer can reduce the shrinkage and deformation of the carbon fiber during the carbonization process, help maintain the fiber morphology, reduce the porosity, and ultimately improve the mechanical properties of the carbon fiber; the polystyrene in the core layer decomposes at high temperatures, and hydrogen and oxygen are released in the form of gas, thereby forming a hollow structure inside the carbon fiber.
[0027] The second technical solution of the present invention:
[0028] A coal-based hollow carbon fiber membrane is prepared by the above preparation method.
[0029] Preferably, the inner diameter of the carbon fiber in the coal-based hollow carbon fiber membrane is 180-850 nm; more preferably: 187-209 nm, 209-313 nm, 313-480 nm, 480-542 nm, 584-667 nm, 750-834 nm.
[0030] Preferably, the specific surface area of the coal-based hollow carbon fiber membrane is 200-400 cm 2 g -1 ; Total pore volume is 0.1-0.3cm 3 g -1 , the micropore volume reaches 0.05-0.25cm 3 g -1 .
[0031] The third technical solution of the present invention:
[0032] The application of the above-mentioned coal-based hollow carbon fiber membrane in the preparation of binder-free capacitive deionization electrode materials.
[0033] Beneficial effects: The coal-based hollow carbon fiber membrane prepared by the present invention is used as a capacitive deionization electrode material. On the one hand, its unique hollow structure has a larger specific surface area, which is conducive to improving the utilization rate of active sites, thereby having excellent desalination performance; on the other hand, the hollow carbon fiber modified by oxidized coal has excellent mechanical properties and can be directly used as a self-supporting electrode for capacitive deionization electrode materials. Its three-dimensional conductive network structure can maintain the high conductivity of the electrode, and the high modulus can maintain the structural integrity of the self-supporting electrode during the cycle, significantly improving the service life of the electrode. That is, the coal-based hollow carbon fiber membrane prepared by the present invention is used as a self-supporting electrode material, without the need to use a polymer adhesive, increasing the active material loading, which is conducive to exposing more active sites, improving the utilization rate of active materials, and achieving efficient ion diffusion and storage.
[0034] Compared with the prior art, the present invention has the following advantages and technical effects:
[0035] 1. The present invention introduces oxidized coal into the hollow carbon fiber matrix. On the one hand, the rich oxygen-containing functional groups of the oxidized coal are used to chemically crosslink with polyacrylonitrile to improve the overall mechanical properties of the carbon fiber; at the same time, the microcrystalline structure of the oxidized coal is used to construct graphite microcrystalline domains in the hollow tube wall to improve the desalination kinetics. Therefore, the coal-based hollow carbon fiber prepared by the present invention has a higher specific surface area and better conductivity, thereby showing stronger ion adsorption capacity and better desalination rate in the process of capacitive deionization. At the same time, when it is used as a capacitive deionization electrode material, there is no need to add a binder when preparing the electrode material like the prior art, which avoids its negative impact on the electrochemical properties of the electrode and shows better desalination performance and structural stability.
[0036] 2. The present invention makes full use of the carbon element in coal resources, realizes efficient utilization of resources, simplifies the production process, reduces environmental pollution, and provides a sustainable technical solution for the development of green energy materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0038] Figure 1 The scanning electron microscope images of the hollow carbon fibers prepared in Examples 1-6 and the solid carbon fibers prepared in Comparative Example 1;
[0039] Among them, a is Example 6, bf are Examples 1-5 respectively, and g is Comparative Example 1; in addition, 1 and 2 in a1 and a2 are scanning electron microscope images of the hollow fiber prepared in Example 6 at different scales, and the others are similar;
[0040] Figure 2 N2 adsorption / desorption curves (a) and pore size distribution (b) of the hollow carbon fibers prepared in Examples 1, 3 and 5 and the solid carbon fibers prepared in Comparative Example 1;
[0041] Figure 3 The tensile stress-strain curves of the hollow carbon fibers prepared in Examples 1-6 and the solid carbon fibers prepared in Comparative Example 1;
[0042] Figure 4 The hollow carbon fibers prepared in Example 1 and the solid carbon fibers prepared in Comparative Example 1 were heated to 500 mg / L -1 Desalination capacity change curve (a) and Ragone curve (b) in NaCl solution;
[0043] Figure 5 This is an X-ray diffraction spectrum of the binder-free capacitive deionization electrode material prepared in Example 1;
[0044] Figure 6 This is the Raman graph of the binder-free capacitive deionization electrode material prepared in Example 1;
[0045] Figure 7 This is a physical picture of the binder-free capacitive deionization electrode material prepared in Example 1;
[0046] Figure 8 The conductivity diagram of the binder-free capacitive deionization electrode material prepared in Example 1;
[0047] The inset is the IV curve. DETAILED DESCRIPTION
[0048] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0049] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0050] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0051] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0052] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0053] The present invention provides a method for preparing a coal-based hollow carbon fiber membrane, comprising the following steps:
[0054] Step 1: After the raw coal is subjected to liquid phase oxidation treatment, the precipitate obtained by centrifugal separation is the oxidized coal;
[0055] Step 2, adding polyacrylonitrile and oxidized coal into N,N-dimethylformamide, and then stirring until completely dissolved to obtain a shell spinning solution;
[0056] Adding polystyrene into N,N-dimethylformamide and stirring until completely dissolved to obtain a core layer spinning solution;
[0057] Step 3, the shell layer spinning solution and the core layer spinning solution in step 2 are respectively loaded into completely identical syringes, and a coaxial electrospinning method is adopted to collect the obtained products on aluminum foil to obtain a coal-based hollow carbon fiber precursor;
[0058] Step 4, placing the coal-based hollow carbon fiber precursor obtained in step 3 into a muffle furnace for pre-oxidation treatment, and then placing it into a tubular furnace for carbonization treatment to obtain a flexible hollow carbon fiber membrane.
[0059] In some preferred embodiments, in step 1, the liquid phase oxidation treatment is to oxidize the raw coal by mixed acid. The surface modification makes some carbon atoms oxidized and have rich oxygen-containing functional groups, such as hydroxyl and carboxyl, which is conducive to the dispersion and dissolution of the oxidized coal in the organic solvent. The mixed acid is a solution of 98wt% concentrated sulfuric acid and 68wt% concentrated nitric acid in a volume ratio of 3:1.
[0060] In some preferred embodiments, the raw coal in step 1 is Xinjiang Heishan bituminous coal, which has not been chemically treated.
[0061] In some preferred embodiments, in step 2, the total concentration of oxidized coal and polyacrylonitrile in the shell spinning solution is 10-20wt%. As the amount of oxidized coal added increases, the concentration of the spinning solution will increase. The concentration of the spinning solution directly affects the degree of entanglement of polymer molecular chains in the solution. Only when the molecular chains are sufficiently entangled can continuous fibers be formed under the action of the electric field force.
[0062] The polystyrene concentration in the core layer spinning solution is 20-30wt%.
[0063] In some preferred embodiments, in step 2, oxidized coal and polyacrylonitrile are added to N,N-dimethylformamide, and magnetically stirred at 50-70° C. for 12-24 hours until completely dissolved to obtain a shell spinning solution;
[0064] The polystyrene is added into N,N-dimethylformamide and magnetically stirred at 50-70° C. for 12-24 hours until it is completely dissolved to obtain a core layer spinning solution.
[0065] In some preferred embodiments, in step 3, the coaxial electrospinning parameters are set as follows: the injection speed of the shell spinning solution is 0.1-1.0 mm min -1 The injection speed of the core layer spinning solution is 0.005~0.34mm min -1 , the positive and negative voltages are set to 10-22 kV and -3.0-0 kV respectively; the aluminum foil is placed on the roller, and the roller speed is 50-150 r min -1 , the receiving distance is 10~25cm.
[0066] In some preferred embodiments, in step 3, by fixing the injection speed of the shell layer spinning solution and adjusting the injection speed of the core layer spinning solution, coal-based hollow carbon fibers with different inner diameters can be obtained, and the ratio of the injection speed of the shell layer spinning solution to the injection speed of the core layer spinning solution is 18:(1-6).
[0067] In some preferred embodiments, the ratio of the injection speed of the shell layer spinning solution to the injection speed of the core layer spinning solution is 18:1, 9:1, 6:1, 9:2, 18:5, 3:1, and the inner diameters of the prepared flexible hollow fibers correspond to 187-209nm, 209-313nm, 313-480nm, 480-542nm, 584-667nm, and 750-834nm, respectively; the tensile strengths correspond to 4.62MPa, 4.32MPa, 3.92MPa, 2.73MPa, 2.26MPa, and 2.06MPa, respectively.
[0068] In some preferred embodiments, the pre-oxidation treatment process in step 4 includes: performing the pre-oxidation treatment in a muffle furnace at a pre-oxidation temperature of 280°C, a pre-oxidation time of 1 hour, an air atmosphere, and a temperature of 2°C min -1 Heating from room temperature to 280°C;
[0069] In some preferred embodiments, the carbonization process in step 4 includes: the carbonization process is carried out in a tubular furnace, the carbonization temperature is 800°C, the carbonization time is 2h, the atmosphere is nitrogen, and the temperature is 5°C min -1 The temperature was raised from room temperature to 800°C.
[0070] The present invention also discloses using the above-mentioned coal-based hollow carbon fiber membrane as a binder-free capacitor deionization electrode material, because the addition of oxidized coal improves the mechanical properties and conductivity of the hollow carbon fiber membrane. Furthermore, using it as a binder-free capacitor deionization electrode material can have both mechanical properties and flexibility. As an independent electrode material, it does not require a current collector and a binder, which not only saves the traditional coating process, but also reduces the manufacturing cost of the electrode material.
[0071] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0072] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.
[0073] The raw materials used in the present invention are all purchased from the market.
[0074] The technical solution of the present invention is further illustrated by the following embodiments.
[0075] Example 1
[0076] Step 1, adding raw coal into a mixed acid solution (concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1), and performing liquid phase oxidation treatment for 2 hours, and the precipitate obtained by centrifugal separation is oxidized coal;
[0077] Step 2, adding polyacrylonitrile and oxidized coal to 5 mL of N,N-dimethylformamide at a mass ratio of 1:1 to prepare a solution with a mass fraction of 16.9 wt% (the total mass fraction of polyacrylonitrile and oxidized coal), and magnetically stirring at 60° C. for 12 h until completely dissolved to obtain a shell spinning solution;
[0078] Step 3, adding polystyrene to 5 mL of N,N-dimethylformamide to prepare a solution with a mass fraction of 25.3 wt%, and magnetically stirring at 60° C. for 12 h until completely dissolved to obtain a core layer spinning solution;
[0079] Step 4, the prepared spinning solutions are respectively loaded into 5 mL syringes, the coaxial electrospinning needles are installed, and then spinning is performed under the condition that the ratio of the shell layer spinning solution injection speed to the core layer spinning solution injection speed is 3:1 (such as Figure 1 f), the positive and negative voltages are 18 kV and -2.5 kV respectively, the aluminum foil is placed on a roller, and the roller speed is 100 r min -1 , receiving distance is 20cm;
[0080] Step 5: The prepared hollow carbon fiber precursor is first transferred to a muffle furnace for pre-oxidation at a temperature of 280°C for 1 h in an air atmosphere at 2°C min -1 The temperature was raised from room temperature to 280°C; the pre-oxidized hollow carbon fiber precursor was transferred to a tube furnace for carbonization treatment at a carbonization temperature of 800°C for 2 hours in a nitrogen atmosphere at a rate of 5°C min -1 The temperature was raised from room temperature to 800°C to obtain a coal-based carbon fiber membrane with a hollow structure - HCF (3:1).
[0081] Example 2
[0082] The difference from Example 1 is that in step 4, spinning is carried out under the condition that the ratio of the shell layer spinning solution injection speed to the core layer spinning solution injection speed is 18:1 (e.g. Figure 1 In a), the positive and negative voltages are 14 kV and -2.5 kV respectively, the aluminum foil is placed on the roller, and the roller speed is 100 r min -1 , the receiving distance is 20cm.
[0083] Example 3
[0084] The difference from Example 1 is that in step 4, spinning is carried out under the condition that the ratio of the shell layer spinning solution injection speed to the core layer spinning solution injection speed is 9:1 (e.g. Figure 1 In b), the positive and negative voltages are 15 kV and -2.5 kV respectively, the aluminum foil is placed on the roller, and the roller speed is 100 r min -1 , the receiving distance is 20cm.
[0085] Example 4
[0086] The difference from Example 1 is that in step 4, spinning is carried out under the condition that the ratio of the shell layer spinning solution injection speed to the core layer spinning solution injection speed is 6:1 (e.g. Figure 1 In c), the positive and negative voltages are 16 kV and -2.5 kV respectively, the aluminum foil is placed on the roller, and the roller speed is 100 r min -1 , the receiving distance is 20cm.
[0087] Example 5
[0088] The difference from Example 1 is that in step 4, spinning is carried out under the condition that the ratio of the shell layer spinning solution injection speed to the core layer spinning solution injection speed is 9:2 (e.g. Figure 1 In (d), the positive and negative voltages are 17 kV and -2.5 kV respectively, the aluminum foil is placed on the roller, and the roller speed is 100 r min -1 , the receiving distance is 20cm.
[0089] Example 6
[0090] The difference from Example 1 is that in step 4, spinning is carried out under the condition that the ratio of the shell layer spinning solution injection speed to the core layer spinning solution injection speed is 18:5 (e.g. Figure 1 In e), the positive and negative voltages are 20 kV and -2.5 kV respectively, the aluminum foil is placed on the roller, and the roller speed is 100 r min -1 , the receiving distance is 20cm.
[0091] Comparative Example 1
[0092] Step 1, adding raw coal into a mixed acid solution (concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1), and performing liquid phase oxidation treatment for 2 hours, and the precipitate obtained by centrifugal separation is oxidized coal;
[0093] Step 2, adding polyacrylonitrile and oxidized coal to 5 mL of N,N-dimethylformamide at a mass ratio of 1:1 to prepare a solution with a mass fraction of 16.9 wt%, and stirring magnetically at 60° C. for 12 h until completely dissolved to obtain a spinning solution;
[0094] Step 3: Load the prepared spinning solution into a 5 mL syringe, install the electrospinning needle, and then prepare solid carbon fibers by electrospinning at a speed of 0.1 mm min. -1 The positive and negative voltages are 13°C and -2.5kV respectively. The aluminum foil is placed on the roller and the roller speed is 100r min -1 , receiving distance is 20cm;
[0095] Step 4: The prepared solid carbon fiber precursor is first transferred to a muffle furnace for pre-oxidation at a temperature of 280°C for 1 h in an air atmosphere at 2°C min -1 The temperature was raised from room temperature to 280°C; the pre-oxidized carbon fiber precursor was transferred to a tube furnace for carbonization treatment at a carbonization temperature of 800°C for 2 hours in a nitrogen atmosphere at a rate of 5°C min -1 The temperature was raised from room temperature to 800°C to obtain a coal-based carbon fiber membrane-CF (such as Figure 1 g), with a specific surface area of 271.95m 2 g -1 .
[0096] Figure 1 The scanning electron microscope images of the hollow carbon fibers prepared in Examples 1-6 and the solid carbon fibers prepared in Comparative Example 1; wherein a is Example 6, bf are Examples 1-5 respectively, and g is Comparative Example 1; in addition, 1 and 2 in a1 and a2 are scanning electron microscope images of the hollow fibers prepared in Example 6 at different scales, and the same is true for the others; from Figure 1 It can be seen that the carbon fibers prepared in Examples 1-6 of the present invention are hollow structures.
[0097] Figure 2 The N2 adsorption / desorption curves and pore size distribution diagrams of the hollow carbon fibers prepared in Examples 1, 3 and 5 and the solid carbon fibers prepared in Comparative Example 1 are shown. The specific surface area of the hollow carbon fiber membranes prepared in Examples 1, 3 and 5 is 200-400 cm 2 g -1 ; Total pore volume is 0.1-0.3cm 3 g -1 , the micropore volume reaches 0.05-0.25cm 3 g -1 .
[0098] Figure 3 The tensile stress-strain curves of the hollow carbon fibers prepared in Examples 1-6 and the solid carbon fibers prepared in Comparative Example 1 are as follows; as can be seen from the figure, as the hollow inner diameter increases, the mechanical properties of the coal-based hollow carbon fibers decrease, but the tensile strength of the coal-based hollow carbon fibers with the largest inner diameter can also reach 2.06 MPa.
[0099] Comparative Example 2
[0100] Refer to the preparation process of FUSFM-0.15 solid fiber material prepared in Example 1 of the existing patent CN 118477492 A.
[0101] Comparing the coal-based hollow carbon fiber membrane prepared in Example 1 of the present invention with the coal-based fiber membrane prepared in Comparative Example 2, there are the following differences: ① The spinning technology and the preparation target are different. The oxidized coal in Comparative Example 2 is used for core layer spinning, and the shell layer spinning liquid is candle ash to prepare solid fiber material; the present invention uses oxidized coal for shell layer spinning liquid to prepare carbon fiber with hollow structure. There is no report on coal-based hollow carbon fiber technology at present; ② The processing properties of the materials are completely different. Comparative Example 2 is directly used as an oil-water separation material after pre-oxidation treatment at 300°C. Its fiber material is essentially a pre-oxidized polyacrylonitrile fiber material with intrinsic electronic insulation. The core of the material lies in the graded rough structure of candle ash on the fiber surface, which improves the roughness and realizes oil-water separation. The role of oxidized coal in carbon fiber is to provide a better fiber skeleton structure; the hollow carbon fiber finally obtained in Example 1 of the present invention is a carbon material that has been subjected to high-temperature treatment at 600-900°C under inert gas, and has excellent electrical conductivity. Figure 6 It can also be seen that ID / IG = 1.03, indicating that the coal-based hollow carbon fiber membrane prepared in Example 1 not only has certain defects, but also maintains the ordered carbon of the graphite structure; Figure 8 It can be seen that the conductivity of Example 1 reaches 4443.8S m -1 , has excellent conductivity, and can be used as an electrode material in the field of electrochemistry. In particular, the specific surface area of the hollow carbon fiber prepared with oxidized coal as the shell in Example 1 of the present invention reaches 378.30 cm 2 g -1 , with a total pore volume of 0.20 cm 3 g -1 , with a large specific surface area and rich pore structure; the hollow carbon fiber uses oxidized coal as the carbon source, which improves the mechanical properties of the fiber and forms graphite microdomains, improves the conductivity of the carbon fiber, and improves the adsorption kinetics of sodium ions, and can be prepared into a self-supporting electrode material with cycle stability.
[0102] Effect verification
[0103] The coal-based hollow carbon fiber membrane prepared in Example 1 of the present invention and the solid carbon fiber prepared in Comparative Example 1 were cut into 4*4 cm squares (such as Figure 7 As shown), it is used as an electrode material for capacitive deionization, and the electrode material is subjected to a desalination test.
[0104] Figure 4 The hollow carbon fibers prepared in Example 1 and the solid carbon fibers prepared in Comparative Example 1 were heated to 500 mg / L -1 Desalination capacity change curve (a) and Ragone curve (b) in NaCl solution; Figure 4 It can be seen that at 1.2V, for 500mg L -1The desalination capacity and maximum desalination rate of NaCl solution increased from 23.12 mg g for solid carbon fiber (CF) -1 and 0.80 mg g -1 min -1 Increased to 37.22 mg g -1 and 3.02 mg g -1 min -1 .
[0105] Figure 5 is the X-ray diffraction spectrum of the binder-free capacitive deionization electrode material prepared in Example 1; Figure 5 It can be seen that the material has broad peaks near 23° and 43°, corresponding to the (002) and (100) crystal planes of graphite, respectively, indicating that the coal-based hollow carbon fibers are mainly composed of amorphous carbon.
[0106] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a coal-based hollow carbon fiber membrane, characterized in that: The following steps are involved: According to the injection speed ratio of the shell layer spinning solution and the core layer spinning solution being 18:(1-6), a hollow fiber precursor is collected on an aluminum foil by a coaxial electrospinning method, and then pre-oxidized and carbonized in sequence to obtain the coal-based hollow carbon fiber membrane; The shell spinning solution contains oxidized coal and polyacrylonitrile; The core spinning solution contains polystyrene.
2. The method for preparing a coal-based hollow carbon fiber membrane according to claim 1, characterized in that: The push injection speed ratio is 18:1, 9:1, 6:1, 9:2, 18:5 or 3:
1.
3. The method for preparing a coal-based hollow carbon fiber membrane according to claim 1, characterized in that: The total concentration of oxidized coal and polyacrylonitrile in the shell spinning solution is 10-20wt%; The polystyrene concentration in the core layer spinning solution is 20-30 wt %.
4. The method for preparing a coal-based hollow carbon fiber membrane according to claim 3, characterized in that: The mass ratio of the oxidized coal to polyacrylonitrile is 1:
1.
5. The method for preparing a coal-based hollow carbon fiber membrane according to claim 1, characterized in that: The condition parameters during the coaxial electrospinning process are: The injection speed of the shell spinning solution is 0.1-1.0 mm min -1 The injection speed of the core layer spinning solution is 0.005~0.34mm min -1 ; The positive and negative voltages are set to 10-22 kV and -3.0-0 kV respectively; the aluminum foil is placed on a roller, and the roller speed is 50-150 r min -1 , the receiving distance is 10~25cm.
6. The method for preparing a coal-based hollow carbon fiber membrane according to claim 1, characterized in that: The conditions in the pre-oxidation process are: In air atmosphere, at 2℃min -1 The temperature was raised from room temperature to 280°C and the pre-oxidation treatment was performed at this temperature for 1 hour.
7. The method for preparing a coal-based hollow carbon fiber membrane according to claim 1, characterized in that: The conditions during the carbonization process are: In an inert atmosphere, at 5 °C min -1 The temperature was raised from room temperature to 800°C and carbonized at this temperature for 2 h.
8. A coal-based hollow carbon fiber membrane, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.
9. The coal-based hollow carbon fiber membrane according to claim 8, characterized in that: The inner diameter of the coal-based hollow carbon fiber membrane is 180-850nm.
10. Use of the coal-based hollow carbon fiber membrane according to claim 8 or 9 in preparing a binder-free capacitive deionization electrode material.
Citation Information
Patent Citations
Crack modified hollow carbon nanowire and preparation method thereof
CN117431665A